A critique and reframing of personality in labour market theory: Locus of control and labour market outcomes - Eileen Trzcinski; Elke Holst (Institute for the Study of Labor (IZA), 2011)
This article critically examines the theoretical arguments that underlie the literature linking personality traits to economic outcomes and provides empirical evidence indicating that labour market outcomes influence personality outcomes. Based on data from the German Socio-Economic Panel, we investigated the extent to which gender differences occur in the processes by which highly positive and negative labour market outcomes are determined and in the processes underlying the development of one particular aspect of personality, locus of control. Gender differences were more pronounced in the results for years in managerial/ leadership positions than for locus of control. Negative labour market states were also marked by gender differences. We conclude by arguing that an explicitly value-laden analysis of the rewards associated with personality within the labour market could expose areas where the gendered nature of rewards by personality serves to perpetuate power relationships within the labour market.
urn:nbn:de:101:1-201111213177
Keywords: J01; J16; J24; J71; B54; 330; labour market theory; power; gender; personality traits; locus of control; SOEP; Persönlichkeitspsychologie; Arbeitsmarkt; Berufliche Integration; Kritik; Geschlecht; Deutschland